On the Different Meanings of the Term Law (Zakon) in Saint Sabba’s Life of Saint Simon - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In mediaeval Serbian law the central legal term zakon (law) indicated a generally obligatory rule (regula iuris) which was usually not a result of the activity of a monarch as ultimate holder of state power. Even where a law was made by state authority such a legal rule had primarily the appearence of a customary legal provision, regulating the conditions within one particular manor (vlastelinstvo) rather than within the whole national territory. Otherwise such laws prescibed the legal position of different categories of inhabitants and identified particular rules of status. Sometimes a law would be introduced to regulate one paricular problem. The concept of law in this period also includes a legal rule derived from custom or from a private contract. Each of these uses can be illustrated from many hundreds of cases from several sources. The use of the term zakon (law) was present in the literary sources as well, such is The Life of Saint Simon (biography of Stefan Nemanja, founder of Serbian mediaeval dynasty Nemanjić), written by his youngest son Rastko, bether known under his monastic name Sabba (Sava). In Sabba’s hagiography of his father we found the term zakon six times. Discribing the State Council (Državni sabor) that had to decide who will be Nemanja’s successor on the throne, Sabba writes that his father pronounced, among other, the following words: „My sons, do not forget the orthodox law that I established.“ The term orthodox law means here orthodox faith, that was established in Serbia after persecutions of Bogomilian heresy. For the second time, term zakon was used in the meaning of monarch’s order. Nemanja says to his sons not to forget his laws. Further, giving the instructions to his sons, Nemanja use the citation from the Bible (The Book of Proverbs or Proverbs of Solomon 3, 1-18), where the term zakon corresponds to the latin ius, not lex. Hereinafter the word zakon means Torah or Pentateuch, the first five books of Bible (citation from the Gospel According to Matthew, 22,40). Next time the term zakon was used as the translation of the Greek word παιδεία (The Book of Proverbs, 1, 8) meaning teaching, advice, lesson, education. Finally, the word zakon means iustice, as the translation of the Greek text of the Book of Proverbs (9, 10).